Triparental ageing in a laboratory population of an insect with maternal care. (24th August 2022) - Cope, Hilary; Ivimey-Cook, Edward R; Moorad, Jacob
Abstract: Parental age at reproduction influences offspring size and survival by affecting prenatal and postnatal conditions in a wide variety of species, including humans. However, most investigations into this manifestation of ageing focus upon maternal age effects; the effects of paternal age and interactions between maternal and paternal age are often neglected. Furthermore, even when maternal age effects are studied, pre- and post-natal effects are often confounded. Using a cross-fostered experimental design, we investigated the joint effects of pre-natal paternal and maternal and post-natal maternal ages on five traits related to offspring outcomes in a laboratory population of a species of burying beetle, Nicrophorus vespilloides . We found a significant positive effect of the age of the egg producer on larval survival to dispersal. We found more statistical evidence for interaction effects, which acted on larval survival and egg length. Both interaction effects were negative and involved the age of the egg-producer, indicating that age-related pre-natal maternal improvements were mitigated by increasing age in fathers and foster mothers. These results agree with an early study that found little evidence for maternal senescence, but it emphasizes that parental age interactions may be an important contributor to ageing patterns. We discuss how the peculiar life history of this species may promote selection to resist the evolution of parental age effects, and how this might have influenced our ability to detect senescence. Abstract : Recent attention within the field of ageing has focused on the relationship between the age of parents and the quality of offspring, but the picture that is emerging is that the presence of this aspect of ageing is highly variable. We describe a laboratory experiment that independently measured effects of maternal and paternal age effects on the fitness traits of larvae and female foster mothers in a species of insect that feeds its young during their development as larvae.